Comparative Study of Gaskets Thickness in Piping System at UTHM Biodiesel Plant Using Finite Element Analysis (FEA) - Hazritauding, Muhammad Amiriqbal; Bachik Abu Bakar (Progress in Engineering Application and Technology, 2022)
This study is carried out as a matter of mechanism just to help the learning process to all students of University Tun Hussein Onn Malaysia (UTHM) generally and especially the students of Mechanical Engineering Technology (Plant). First, the objective of this project is to compare the von mises stress, displacement and equivalent strain of the gaskets thickness in the piping system. Next, the objective of this project is to study gaskets thickness in the piping system using the simulation technique. There are four thickness gaskets for this project that is 1mm, 2mm, 5mm and 8mm. Neoprene rubber is the material for the gaskets and the pressure in this piping system is 4bar. The thickness of gaskets will be studied by analysis using SolidWorks software to predict the mechanical properties of gaskets to reduce operation and maintenance cost. The method analysis that will be used is Finite Element Analysis (FEA). Through the data from analysis, the result show that gaskets 8mm has the maximum von mises stress and displacement but minimum for equivalent strain while gasket 1mm has the minimum von mises stress and displacement but maximum for equivalent strain. For the conclusion, its found that 2mm gasket thickness is the standard used on piping systems using water as a working fluid.